On travelling wave solutions of some nonlinear evolution equations - İnç, Mustafa; Evans, DJ (Taylor & Francis Ltd, 2004)
A method to construct the exact solutions of some nonlinear evolution equations is presented by the hyperbolic function method. The efficiency of the method can be demonstrated by some nonlinear PDEs such as the Benjamin-Bona-Mahony equation, the coupled KdV and MKdV equations. New exact travelling wave solutions are presented. In addition, the properties of these equations are shown with figures.
Keywords: hyperbolic function method; nonlinear evolution equation; travelling wave solution; symbolic computation